2002
DOI: 10.1002/1521-3757(20020617)114:12<2217::aid-ange2217>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A Click Chemistry Approach to Tetrazoles by Huisgen 1,3-Dipolar Cycloaddition: Synthesis of 5-Acyltetrazoles from Azides and Acyl Cyanides We thank the National Institute of General Medical Sciences, National Institutes of Health (GM-28384), the National Science Foundation (CHE-9985553), the Skaggs Institute for Chemical Biology for a Predoctoral Fellowship (Z.D.), and the W. M. Keck Foundation for financial support.

Abstract: The preceding communication [1] describes the facile [23] cycloaddition of azides and p-toluenesulfonyl cyanide to form 5-sulfonyl tetrazoles, interesting compounds in their Together with the known substitutions of the resulting sulfonyl tetrazoles, the two-step sequence is formally equivalent to regioselective cycloadditions of azides with a wide variety of nitriles. Further studies on the scope of this chemistry will be reported. [20] Experimental Section Note: Many low-molecular-weight azides are known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Most recent studies on the subject rely on a classical paper in which benzyl azide derivatives and alkyl cyanoformates (ROCO‐CN) were heated without solvent at 130 °C in a sealed tube;3 tetrazoles of type 2 can be achieved in roughly 60–70 % yields, at best. To reduce the hazards inherent to heating these polynitrogenated starting materials and products, Demko and Sharpless investigated a “click chemistry” approach4, 5 by using mainly acyl cyanides (RCO‐CN) and organic azides, which allowed them to obtain compounds of type 3 (1,5‐disubstituted) under solvent‐free conditions, without catalysts, at 120 °C 4a. From the more reactive p ‐toluenesulfonyl cyanide, excellent yields of 1,5‐disubstituted tetrazoles were similarly obtained at 80–100 °C 4b…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recent studies on the subject rely on a classical paper in which benzyl azide derivatives and alkyl cyanoformates (ROCO‐CN) were heated without solvent at 130 °C in a sealed tube;3 tetrazoles of type 2 can be achieved in roughly 60–70 % yields, at best. To reduce the hazards inherent to heating these polynitrogenated starting materials and products, Demko and Sharpless investigated a “click chemistry” approach4, 5 by using mainly acyl cyanides (RCO‐CN) and organic azides, which allowed them to obtain compounds of type 3 (1,5‐disubstituted) under solvent‐free conditions, without catalysts, at 120 °C 4a. From the more reactive p ‐toluenesulfonyl cyanide, excellent yields of 1,5‐disubstituted tetrazoles were similarly obtained at 80–100 °C 4b…”
Section: Methodsmentioning
confidence: 99%
“…[d] Anhydrous and pentahydrate, with identical results. Addition of sodium ascorbate (aqueous solution or in t BuOH/H 2 O)4a, b, 5e is not recommended, as partial hydrolysis of EtOCO‐CN (EWG‐CN) takes place.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximity of the CO and CN groups in acyl cyanides enhances the electrophilicity of both functionalities. Although the reactions usually occur at the carbonyl group,19 attack at the CN moiety by soft nucleophiles such as H 2 S20 and azides21 are known. Here we found that the zirconium‐mediated reaction of TBS‐substituted butadiyne 1 a with PhCOCN provided azazirconacyclopentene 16 a in 29 % yield (Table 2, entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…Among the most versatile methods for obtaining tetrazoles are the Ugi-azide four-component reaction (Ugi-azide-4CR) [1416] and the 1,3-dipolar cycloaddition of azides with (acyl)cyanides [1718]. The Ugi-azide-4CR enables the incorporation of three different diversity-generating sites (Scheme 1), a feature that has been exploited for the construction of libraries of tetrazole-based compounds with potential bioactivity [912 19].…”
Section: Introductionmentioning
confidence: 99%